Cara Baru Memandang Prinsip Non-Intervensi ASEAN dalam Menilik Kasus Rohingya - Ajeng Wirachmi (Jurnal Syntax Admiration, 2023)
This research aims to propose a fresh perspective on ASEAN's non-intervention principle through the analysis of the Rohingya case. The Rohingya case represents a humanitarian crisis complexity in the Myanmar region that necessitates serious consideration from ASEAN as a regional body. This research employs a multidisciplinary approach involving political analysis, international law, and international relations theory. The study argues that ASEAN's non-intervention principle should not be interpreted as a reluctance to intervene in cases of human rights violations that threaten regional security. Instead, the research advocates for a more proactive and responsive approach from ASEAN towards humanitarian situations resulting in mass suffering, such as the Rohingya case. The findings of this research provide new insights into how ASEAN can modernize its approach to the non-intervention principle, emphasizing the importance of human rights protection as an integral part of regional stability and peace. This research also proposes concrete recommendations regarding steps that ASEAN can take in addressing similar cases in the future, thereby strengthening ASEAN's role and relevance in the context of global humanitarian issues.